COVID-19 Vaccination in Cancer Patients: A Review Article. (1st June 2022) - Mekkawi, Rana; Elkattan, Bassant A.; Shablak, Alaaeldin; Bakr, Mohammad; Yassin, Mohamed A.; Omar, Nabil E.
Coronavirus disease 2019 (COVID-19) infection is caused by severe acute respiratory syndrome coronavirus 2. Adults with cancer are immunocompromised due to several causes including cancer itself and immunosuppressive therapy. Thus, cancer patients are more susceptible to develop COVID-19 infection. As COVID-19 vaccines became available, patients with cancer would benefit from receiving the vaccine. This article aims to review the recent evidences and recommendations about COVID-19 vaccination in cancer patients. Current guidelines recommend that patients with cancer should have the priority to receive the vaccine given their immunocompromised state. The timing of administration varies depending on cancer type and treatment. Generally, the vaccine should be given before starting the chemotherapy if possible or in between chemotherapy cycles and away from nadir phase. For other cancer treatments, it is recommended to give the vaccine when there is evidence of blood count recovery. In general, induction therapy and treatment for newly diagnosed patients should not be delayed for the vaccination purpose. It is noteworthy to mention that cancer patients especially those with hematologic malignancies might have absented or attenuated response to the vaccine due to their pathophysiological status. On the other hand, the current vaccine guidelines have been criticized for lacking evidence on some important topics that need to be addressed. Firstly, some vaccines have been granted an emergency use authorization, prior to the usual comprehensive safety and efficacy evaluation process. Secondly, specific populations including cancer patients were excluded from the approval trials for safety reasons. Finally, some recommendations regarding the COVID-19 vaccines are extrapolated from other vaccines studies. Further studies are required to fill these gaps and observational studies that include cancer patients are warranted to have a better understanding of the safety and efficacy of the vaccines in cancer patients.